The performance of OFDM in mobile radio channel - Purnamirza, Teddy (2005)
OFDM as a transmission technique has been known having a lot of strengths compared to any other transmission technique, such as its high spectral efficiency, its robustness to the channel fading, its immunity to impulse interference and its ability in handling very strong echoes. It is mentioned in several papers and by the OFDM theory itself that because of its strength, OFDM can overcome the effect of several radio impairment factors such as the effect of AWGN, impulse noise, multipath fading, etc. In addition, several papers proposed OFDM as a transmission technique either in fixed or mobile radio channel. The efficacy of OFDM implementation in many areas such as DAB (Digital audio Broadcasting), DVB (Digital Video Broadcasting) and Wireless LAN has gained its popularity. This project is to study and investigate the effect of some radio channel impairment factors to the performance of OFDM as well as to study and investigate the performance of OFDM in mobile radio channel including rural channel, urban channel, terrain channel and rician channel.